直线齿廓内齿轮传动副的齿形设计及运动仿真 - 王全先; 南昀 (Jixie chuandong)
The equation of a curve of conjugate external gear tooth profile is derived for linear internal gearing. The geometry size of a gearing is determined by the general formulae and the maximum of profile’s half angle γ is put forward. Based on 3-D mode of Pro/E, the movement simulation of the gearing is carried on, it is shown that the gearing meshing is continuous and noninterference.